Dynamics of the Indonesian Sharia Stock Index and Macroeconomic Factors: An Analysis Using the Vector Error Correction Model (VECM) - Zulaiha Fatimah; Trischa Relanda Putra (Journal of Business and Management Review, 2025)
Research Aims: This study examines how several macroeconomic factors influence shifts in the Indonesian Sharia Stock Index (ISSI). The analyzed factors include M2, currency exchange rates, the Industrial Production Index (IPI), inflation, the BI Rate, and global gold prices. Design/methodology/approach: The study employs a quantitative approach using monthly secondary data from 2014 to 2023. The Vector Error Correction Model (VECM) is used to determine both short-term and long-term relationships between variables. Additionally, Variance Decomposition (VD) and Impulse Response Function (IRF) analysis are utilized to assess the interactions among the variables. Research Findings: The study finds that M2, exchange rates, IPI, inflation, and gold prices exhibit long-term effects on ISSI, while the BI Rate does not. In the short term, ISSI is primarily influenced by IPI. The IRF analysis indicates that ISSI responds positively to shocks in M2 and gold prices but remains relatively stable concerning exchange rates and the BI Rate. Theoretical Contribution/Originality: The findings offer crucial insights for investors and regulators in understanding the macroeconomic dynamics influencing the Indonesian Sharia stock market. The study enhances the comprehension of how economic variables interact with ISSI, contributing to more informed investment and policy decisions. Keywords: VECM, Macroeconomics, Indonesian Sharia Stock Index.